Modelling and validation of synthesis of poly lactic acid using an alternative energy source through a continuous reactive extrusion process - Dubey, Satya P.; Abhyankar, Hrushikesh; Marchante, Veronica; Brighton, James L.; Blackburn, Kim; Temple, Clive; Bergmann, Björn; Trinh, Giang; David, Chantal (MDPI, 2016)
PLA is one of the most promising bio-compostable and bio-degradable thermoplastic polymers made from renewable sources. PLA is generally produced by ring opening polymerization (ROP) of lactide using the metallic/bimetallic catalyst (Sn, Zn, and Al) or other organic catalysts in a suitable solvent. In this work, reactive extrusion experiments using stannous octoate Sn(Oct)2 and tri-phenyl phosphine (PPh)3 were considered to perform ROP of lactide. Ultrasound energy source was used for activating and/or boosting the polymerization as an alternative energy (AE) source. Ludovic® software, designed for simulation of the extrusion process, had to be modified in order to simulate the reactive extrusion of lactide and for the application of an AE source in an extruder. A mathematical model for the ROP of lactide reaction was developed to estimate the kinetics of the polymerization process. The isothermal curves generated through this model were then used by Ludovic software to simulate the “reactive” extrusion process of ROP of lactide. Results from the experiments and simulations were compared to validate the simulation methodology. It was observed that the application of an AE source boosts the polymerization of lactide monomers. However, it was also observed that the predicted residence time was shorter than the experimental one. There is potentially a case for reducing the residence time distribution (RTD) in Ludovic® due to the ‘liquid’ monomer flow in the extruder. Although this change in parameters resulted in validation of the simulation, it was concluded that further research is needed to validate this assumption.
Keywords: alternative energy; bio-degradable; reactive extrusion; metal catalyst; mathematical modelling; poly lactic acid (PLA); ring opening polymerization (ROP)